Regional integration and future cooperation initiatives in the Eurasian economic union - Lagutina, M. L., 1981- (Advances in finance, accounting, and economics (AFAE) book series., 2020)
"This book examines regional integration and future cooperation initiatives in the Eurasian economic union"--Provided by publisher"--